Beyond the COVID-19 Shutdown: A Causal Analysis of the Long-Term Impact on Pediatric Dental Health - Zhang, Ranya; Quo, Brayden; Schmidt, Jacob (Journal of the California Dental Association, 2025)
Background Health care disruptions due to the COVID-19 pandemic raised concerns about delayed pediatric dental care and its short- and long-term consequences, particularly for children with less established care routines.Methods We tracked 2,857 regular pediatric patients over four years, applying a difference-in-differences (DiD) approach to study within-patient changes in visit frequency, procedures performed, and treatment costs across preschoolers, elementary schoolers, and teenagers.Results The pandemic had long-lasting effects on care patterns. Visit frequency declined for all age groups and stayed lower even three years post-pandemic, with a notable drop of over 20% among preschoolers. Meanwhile, procedures and total fees increased in the long term for older children, with costs rising by nearly 30%.Conclusions Even a brief disruption in dental care led to lasting reductions in visit frequency and increased treatment complexity and costs, particularly among younger children. These patterns persisted even three years later.Practical Implications Dental providers and policymakers should prioritize early outreach and establishment of routine care to prevent delayed treatment from escalating into more costly and complex dental needs.